Assessing sustainability on the modern Silk Road: An objective weighting methodological approach - Chia-Nan Wang; Hoang-Kha Nguyen; Nhat-Luong Nhieu (PLoS ONE, 2025)
The Silk Road Economic Belt (SREB), a major 21st-century initiative, aims to revive the historic Silk Road by connecting Asia, Europe, and Africa through a network of trade and cultural exchange routes. This study aims to assess sustainable development across sixteen countries situated in South Asia, West Asia, and Africa—regions that are central to the SREB but face diverse environmental and socio-economic challenges. To achieve this, a novel hybrid multi-criteria decision-making approach is proposed, combining the Method based on the Removal Effects of Criteria (MEREC) and Operational Competitiveness Ratings Analysis (OCRA). The MEREC method is used to determine objective weights for sustainability indicators by evaluating the impact of each criterion’s exclusion, while OCRA is employed to evaluate and rank countries based on both beneficial and non-beneficial indicators. The findings reveal significant disparities in sustainability performance across the studied countries. Israel ranked highest in sustainability, followed by Sri Lanka and Nepal, while India showed the lowest performance. These results provide valuable benchmarks and strategic insights for regional policy planning and sustainable development efforts within the SREB framework.